Fodder Production and Utilization Strategies for Sustainable Livestock Development in India - Misra, Arun Kumar (Annals of Arid Zone, 2019)
Feed resources for livestock in India are becoming important due to scarce supply particularly in dry regions because of seasonal variability in rainfall. Due to increasing human and livestock population, the pressure on land is increasing day-by-day and the existing natural resources are deteriorating and creating land degradation. Livestock production systems are complex and mostly based on indigenous traditional knowledge and socio-economic considerations, often guided by available feed resources at their disposal. Integration of fodder production with existing cropping system has tremendous promise to sustain the ever-growing livestock population. In this paper an attempt is being made to review the fodder availability, and discuss the various options for fodder production and their utilization for sustainable livestock production in India. Key words: Forage yield, common property resources, socio-economic.